Screening and evaluation of local bacteria isolated from shellfish as potential probiotics against pathogenic Vibrios - M. Y., Jasmin; Wagiman, Hazimah; Tan, Ai Yin; Md Yasin, Ina Salwany; Mohd Daud, Hassan; Abd Karim, Murni Marlina (Triveni Enterprises, 2016)
The present study was carried out to isolate, screen and evaluate potential candidates of local bacteria isolated from tiger shrimp Penaeus monodon and slipper cupped oysters Crassostrea iredalei as probiotics in shellfish aquaculture. A total of 144 of bacteria were successfully isolated from the intestine and stomach of 20 tails of healthy adult tiger shrimp P. monodon, while 136 were successfully isolated from the digestive tract, gills and inner shells of 10 healthy adult C. iredalei. The number of potential isolates was narrowed down to two from tiger shrimp, and one from slipper cupped oyster after in vitro screening assays. The three isolates, labeled as G11, I24 and S66, were identified as Virgibacillus sp., Bacillus sp. and Exiquobacterium sp., respectively, using 16S rDNA gene analysis. The antagonistic ability of the isolates towards Vibrio alginolyticus and Vibrio harveyi were conducted in stagnant and liquid modes via spot lawn and broth co-culture assay, respectively. In these assays, all the potential probionts were inhibitory to both pathogenic vibrios. In the in-vivo assay, Artemia was used as host and treated with different concentrations of potential probionts (10⁴, 10⁶ and 10⁸ CFU ml⁻¹), and challenged with V. alginolyticus ana V. harveyiat 10⁵ CFU ml⁻¹ Respectively, Artemia treated with probiont Gl 1 at all concentrations and challenged with V. alginolyticus had increased survival (70-80 %), which was significantly higher as compared with group with only the pathogen (20 %). Meanwhile, probiont I24 increased the survival of Artemia by 70 % at a concentration of 10⁸ CFU ml⁻¹ after being challenged with V. alginolyticus and Artemia treated with 10⁶ CFU ml⁻¹ of probiont S66 had increased survival of 90% after being challenged with V. harveyi. Thus, the three isolates might have potential applications as probiotics in shellfish aquaculture against vibriosis.